Exploring the Dynamics of Academic Achievement in End of Semester Assessment Based on Class and Gender Using a Two Way ANOVA Approach - Wigbertus Ngabu; Putri Yuanita; Elmawati Elmawati; Suci Andriani; Yusa Putra (JPMI (Jurnal Pendidikan Matematika Indonesia), 2026)
The evaluation of learning outcomes is an essential component of higher education because it reflects learning achievement and the effectiveness of the instructional process. This study aims to analyze the dynamics of students’ academic performance in the final semester examination of the Basic Statistics course based on class (A, B, C) and gender (male, female). The study employed an explanatory quantitative approach with a factorial design and was analyzed using a two-way analysis of variance (two-way ANOVA). Assumption testing indicated that the residuals were normally distributed (Shapiro–Wilk p = 0.0854) and that variances across groups were homogeneous (Levene p-value = 0.6468), confirming that the ANOVA prerequisites were satisfied. The ANOVA results showed that class had a statistically significant effect on final examination scores (F(2,104) = 2.956; p = 0.00562) and that gender also had a statistically significant effect (F(1,104) = 0.704; p = 0.0032), whereas the class × gender interaction was not statistically significant (F(2,104) = 1.355; p = 0.0626). Post hoc analysis using Tukey’s HSD revealed that differences across classes were primarily driven by the contrast between Class C and Class A (p-adj = 0.0443), while gender-based differences showed a consistent pattern across classes (p-adj = 0.0069). These findings were supported by boxplots and interaction plots that displayed score distributions consistent with the inferential results. Overall, the study indicates that variation in students’ academic performance in the final semester evaluation is independently influenced by class and gender. The findings are expected to inform more data-driven academic decision-making and contribute methodologically to the application of statistical analysis. Based on these results, the study program is advised to standardize instructional implementation and evaluation across classes and to provide more targeted learning support for groups of students who consistently demonstrate lower achievement, so that learning gaps can be reduced in a data-driven manner.Eksplorasi Dinamika Prestasi Akademik pada Evaluasi Akhir Semester Berdasarkan Kelas dan Gender Menggunakan Pendekatan ANOVA Dua ArahABSTRAKEvaluasi hasil belajar merupakan komponen penting dalam pendidikan tinggi karena mencerminkan capaian pembelajaran serta efektivitas proses pembelajaran. Penelitian ini bertujuan menganalisis dinamika prestasi akademik mahasiswa pada ujian akhir semester mata kuliah Statistika Dasar berdasarkan faktor kelas (A, B, C) dan gender (laki-laki, perempuan). Penelitian menggunakan pendekatan kuantitatif eksplanatori dengan desain faktorial dan dianalisis melalui Analisis Varians Dua Arah (two-way ANOVA). Uji asumsi menunjukkan residual berdistribusi normal (Shapiro–Wilk ) dan varians antar-kelompok homogen (Levene p-value = 0.6468), sehingga prasyarat ANOVA terpenuhi. Hasil ANOVA menunjukkan bahwa faktor kelas berpengaruh signifikan terhadap skor ujian akhir semester  dan faktor gender juga berpengaruh signifikan , sedangkan interaksi kelas×gender tidak menunjukkan pengaruh yang signifikan . Uji lanjut Tukey HSD mengungkapkan bahwa perbedaan capaian antar kelas terutama didorong oleh perbedaan Kelas C dan Kelas A (p-adj = 0.0443), sementara perbedaan berdasarkan gender menunjukkan kecenderungan yang konsisten di seluruh kelas  Temuan ini diperkuat oleh boxplot dan interaction plot yang menampilkan pola distribusi skor sejalan dengan hasil inferensial. Secara keseluruhan, penelitian ini menunjukkan bahwa variasi prestasi akademik mahasiswa dalam evaluasi akhir semester dipengaruhi secara independen oleh faktor kelas dan gender. Hasil penelitian ini diharapkan dapat menjadi dasar pengambilan keputusan akademik yang lebih berbasis data, serta memberikan kontribusi metodologis dalam penerapan analisis statistik.  Berdasarkan temuan tersebut, program studi disarankan melakukan standardisasi implementasi pembelajaran dan evaluasi antar kelas serta menyediakan dukungan belajar yang lebih terarah bagi kelompok mahasiswa yang konsisten menunjukkan capaian lebih rendah agar kesenjangan hasil belajar dapat ditekan secara berbasis data.Kata Kunci :Prestasi akademik mahasiswa; Statistika dasar; Evaluasi pembelajaran; ANOVA